New EMC VPLEX GEO redefines cloud storage. IN Tech101.
EMC makes long-distance storage federation a reality; expands data center boundaries enabling "Access Anywhere".
Keywords: EMC Corporation; Virtual storage (Computer science); VPLEX Geo; Data centers